Cooperation amidst crises: dynamics of media strategic alliance networks between Thailand and Malaysia - Mohd Helmi Abd Rahim,; Badrul Redzuan Abu Hassan,; Novel Lyndon, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2013)
Issues relating to globalization and cross-border cooperation in the contexts of political, economic and trade have been discussed and explored extensively across both developed and developing nations. Nevertheless, not much has been discussed on the role of media in enhancing cooperation between nations. In practice, the media is always looked upon as the crises builder or enhancer. Anyhow, the fact is that different groups of people use the same media content for different reasons. The media can be interpreted in the hands of the users. The media actually is a perfect tool to generate dialogue across borders. In this case, media institutions, which encompassed both electronic media and print media, together with the new media that focused on information and communication technologies, have the capacity to strategically enhance the extent of cooperation between governments, societies and nations. In relation to this, the article has undertaken to examine how media institutions in both countries can play a more proactive role in strengthening bilateral cooperation between Thailand and Malaysia in terms of projecting the political, economic, cultural, and social image of both countries through media coverage encompassing television programs, news, films, advertisements, as well as the new media such as Internet communication. The discussion will be conducted in two levels of analysis, the macro and the micro. The article shall focus on the end results of these two methods by which consumers use the media and the anticipation by the mass communicator. The article also investigates the opportunities of dynamics media strategic alliance in terms of structural, content and the end results of information, by media institutions of both countries.